Characterization of carbon nanotube field effect transistors in vacuum - Sun, Huiyan. (2009)
This report focuses on the characteristics of Carbon Nanotube Field Effect Transistors (CNTFETs) in oxygen under different pressures. The characteristics of CNTFETs are commonly influenced by chemical gases. These gases generally modulate the CNTFET electrode Schottky barrier, which will be discussed in detail in this report. The literature review about the Carbon Nanotube (CNT) and CNTFETs are given, introducing this new technology. The device fabrication process is introduced. The procedures and equipments used for this project are shown. I-V characteristics of CNTFETs under different pressures are the important part in this report. The observation and analysis results are discussed by Schottky barrier modulation, followed by conclusion and recommendation.